Distinct succession patterns of abundant and rare bacteria in temporal microcosms with pollutants. (June 2017) - Jiao, Shuo; Luo, Yantao; Lu, Mingmei; Xiao, Xiao; Lin, Yanbing; Chen, Weimin; Wei, Gehong
Abstract: Elucidating the driving forces behind the temporal dynamics of abundant and rare microbes is essential for understanding the assembly and succession of microbial communities. Here, we explored the successional trajectories and mechanisms of abundant and rare bacteria via soil-enrichment subcultures in response to various pollutants (phenanthrene, n -octadecane, and CdCl2 ) using time-series Illumina sequencing datasets. The results reveal different successional patterns of abundant and rare sub-communities in eighty pollutant-degrading consortia and two original soil samples. A temporal decrease in α -diversity and high turnover rate for β -diversity indicate that deterministic processes are the main drivers of the succession of the abundant sub-community; however, the high cumulative species richness indicates that stochastic processes drive the succession of the rare sub-community. A functional prediction showed that abundant bacteria contribute primary functions to the pollutant-degrading consortia, such as amino acid metabolism, cellular responses to stress, and hydrocarbon degradation. Meanwhile, rare bacteria contribute a substantial fraction of auxiliary functions, such as carbohydrate-active enzymes, fermentation, and homoacetogenesis, which indicates their roles as a source of functional diversity. Our study suggests that the temporal succession of microbes in polluted microcosms is mainly associated with abundant bacteria rather than the high proportion of rare taxa. The major forces (i.e., stochastic or deterministic processes) driving microbial succession could be dependent on the low- or high-abundance community members in temporal microcosms with pollutants. Highlights: The successional mechanisms of abundant and rare bacteria were analyzed. Deterministic processes are the main drivers of the succession of the abundant sub-community. Stochastic processes drive the succession of the rare sub-community. Temporal succession of microbes is mainly associated with abundant bacteria rather than rare taxa.